2012
DOI: 10.1039/c2cp23451c
|View full text |Cite
|
Sign up to set email alerts
|

Gas-to-solid shift of C 1s-excited benzene

Abstract: The gas-to-solid shift of benzene is reported in the C 1s-core level regime, where the C 1s → π*-transition is investigated between 284.0 eV and 286.5 eV. Simultaneous experiments on the gas phase and condensed species are used to determine the gas-to-solid shift within an accuracy of ±5 meV. Specifically, it is observed that the vibrationally resolved C 1s → π*-transition in solid benzene is red-shifted by 55 ± 5 meV relative to the transition of the isolated molecule. Contrary to previously reported experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…The experimental setup is similar to previous work. 3,8,9 The present results cover, however, a significantly wider energy range since the undulator based photon source has become fully tunable, which was not possible in our previous work on SF 6 clusters. 8,9 This provides novel information on the S 2p → 6a 1g -resonance below the edge as well as the S 2p → 4e g -shape resonance.…”
Section: Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…The experimental setup is similar to previous work. 3,8,9 The present results cover, however, a significantly wider energy range since the undulator based photon source has become fully tunable, which was not possible in our previous work on SF 6 clusters. 8,9 This provides novel information on the S 2p → 6a 1g -resonance below the edge as well as the S 2p → 4e g -shape resonance.…”
Section: Methodsmentioning
confidence: 57%
“…1,2 Specifically, free variable size molecular Van-der-Waals clusters have been investigated in the soft X-ray regime. [3][4][5][6][7][8][9] These are regarded as suitable model systems for studying size effects of elementary processes in weakly bound quantum systems as well as cage effects in composite and biological systems. In addition to significant changes in core-to-Rydberg transitions studied by high resolution X-ray spectroscopy, significantly smaller spectral shifts in core-to-valence transitions in molecular clusters have been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known in the previous work that the aromatic π-π interactions cause an energy shift of the π* peak in XAS. [67][68][69] We have also measured C K-edge XAS spectra of benzene clusters in the gas phase, 70 which are formed by an adiabatic gas expansion method, and solid benzene at -193 C, 71 and found that the π* peaks show lower energy shifts compared to those of gas, which is ascribed to different structural properties of clusters compared to the solid. In the present work, we have systematically investigated temperature-dependent changes of ordered structures in liquid benzene by C K-edge XAS with the combination of the MD simulation and inner-shell calculations.…”
Section: •2 Temperature-dependent Structural Changes In Liquidmentioning
confidence: 99%
“…The inset of Fig. 6(a) shows the peak positions of gas phase (G), solid at -193 C (S), 71 and cluster structures (C). 70 The energy shift of liquid benzene at 25.3 C is -26 ± 5 meV relative to the gaseous benzene, which is between the gas and the solid at -193 C. Figure 6(b) shows the energy shift of the π* peak of liquid benzene relative to benzene gas as a function of temperature.…”
Section: •2 Temperature-dependent Structural Changes In Liquidmentioning
confidence: 99%